An Investigation of the Phytochemical Composition and Antimicrobial Activities of Commiphora Africana Stem Bark Extract - I. Jimoh; I. Alhassan; P. O. Asipita; Evinemi, Patience A.; L. A Musa (International Journal of Global Sustainable Research, 2024)
Commiphora africana, a traditional African medicinal plant, has been used to treat various infections. This study investigated the phytochemical composition and antimicrobial activities of its stem bark extract. Phytochemical screening revealed the presence of alkaloids, flavonoids, glycosides, and terpenoids. The extract exhibited significant antimicrobial activity against a panel of microorganisms, including Staphylococcus aureus, Escherichia coli, and salmonella typhi, with MIC values ranging from 0.5-2.5 mg/mL. The antioxidant activity of the extract was also evaluated, showing a high scavenging capacity. The findings suggest that the stem bark extract of Commiphora africana is a potential source of natural antimicrobial and antioxidant agents, supporting its traditional use in medicine. Further studies are needed to isolate and characterize the bioactive compounds responsible for these activities